Desktop Biometric: The Easy way for Biometric Authentication - Kumar, Ravinder; Kalra, Ramneek (International Journal of Computer Sciences and Engineering, 2025)
Biometric is widely used as proper authentication of a person in an organization, Institute and at much more places. This is considered as original identification of one by offering different biometric techniques which includes Hand Biometric, Fingerprint Biometric, Face Biometric, Signature Biometric, Ear Recognition and many more. Considerably, every technique of biometric includes one or other negative outcome that enables one to use more technique to develop pure authentication of person. This paper reflects the use of personal fingerprint scanning biometric that gives proper giveaway of features of person’s identification. The proposed research presents the content in very detailed way from introduction to biometric with specifically concentrated to fingerprint biometric and then integrating that real-time data with JAVA based software testing and developing innovative college student attendance system. The benefits of using proposed software give a new way to allot ids to professors and students with automation of sending attendance with customized options for need.